FEATURES OF ENGLISH TEXTBOOKS FOR THE FIRST-YEAR OF SENIOR HIGH SCHOOL IMPLEMENTING THE 2013-CURRICULUM - Emelda Syafrina; Arono Arono (JOALL (Journal of Applied Linguistics and Literature), 2017)
This research aimed to investigate the quality of English for the First Year of Senior High School Implementing the 2013 Curriculum the academic years 2016/2017. The method applied in this research was descriptive method. Data collection techniques used observation check list. There were three textbooks observed. The aspects that were observed consisted of content, presentation, language, and graphic. The result indicated as follows. For the appropriateness the content of view; there were only two textbooks which belong to ‘good’ category books, namely Pathway to English for Senior High School Grade X, published by Erlangga and Bahasa Inggris SMA/MA/SMK/MAK Kelas X, published by Kemdikbud. An others textbook had ‘fair’ category namely Bahasa Inggris untuk SMA-MA/SMK kelas X, published by Yrama Widya. There was one textbook which was categorized into ‘very good’ presentation, namely Bahasa Inggris SMA/MA/SMK/MAK Kelas X, published by kemdikbud. while two other textbooks, namely Pathway to English for Senior High School Grade X and Bahasa inggris untuk SMA-MA/SMK kelas X had ‘good’ category. Concerning the language aspect, there was one textbook, nemely Bahasa Inggris SMA/MA/SMK/MAK Kelas X had ‘very good’ category. Two other textbooks, namely Pathway to English for Senior High School Grade X and Bahasa inggris untuk SMA-MA/SMK kelas X had ‘good’ category. Concerning the graphic aspect, there were two textbooks which belonged to ‘very good’ category, namely Pathway for Senior High School Grade X and Bahasa Inggris SMA/MA/SMK/MAK Kelas X. An others textbook namely, Bahasa Inggris SMA- MA/ SMK kelas X had ‘good’ category. Thus, three textbooks had good category and be worthy to use because they fulfilled the quality of good textbook.